Making organic coatings greener: Renewable resource, solvent-free synthesis, UV curing and repairability. (15th January 2020) - Wang, Shuaipeng; Wu, Yonggang; Dai, Jinyue; Teng, Na; Peng, Yunyan; Cao, Lijun; Liu, Xiaoqing
Graphical abstract: Synthesis of repairable UV cured coatings from renewable itaconic acid and 2-furoic acid. Highlights: Combination of renewable resource, UV curing process and repairability. The solvent-free condition was taken to synthesize the UV-curable monomers. The prepared coatings showed satisfied comprehensive properties. The scratches on coatings could be repaired quickly simply with the help of heating. Abstract: Using renewable resource to synthesize UV-curable coatings with self-healing properties is of great significance to environmental protection and sustainable development. Herein, two bio-based UV-curable monomers itaconic acid-glycidyl methacrylate (IG) and 2-furoic acid-glycidyl methacrylate (FG) were synthesized from the renewable itaconic acid (IA) and 2-furoic acid (FA) under solvent-free condition. After their chemical structure was confirmed by Fourier Transform Infrared (FT-IR) and Nuclear Magnetic Resonance (NMR), FG was mixed with IG at different ratios to prepare the UV-curing coating films. Their thermal, mechanical and coating properties were investigated in detail. Results showed that the bio-based films with varied properties could be easily obtained by adjusting the weight ratio of IG and FG. Remarkably, they all demonstrated excellent self-healing, repairable and remodel abilities. For the first time, this work reported the bio-based UV-curable coatings with good repair-ability only with the assistance of heating, which should be a remarkable progress towards the sustainable development of organic coatings.